Analisis Buku Bahasa Arab Pegangan Guru dan Siswa Kelas XI Kurikulum 2013 - Muhammad Nashrullah; Mirwan Akhmad Taufiq (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
This study aims to explain the quality of the teacher's handbook and the student's handbook of Arabic book on XI class with curriculum of 2013 printed by the Ministry of Religion in Indonesia. The existence of books has a very important role in learning in schools. In this case, the quality of the textbooks that are used as learning resources also determines the results of the achievement of learning objectives. One of the government policies in implementing the curriculum of 2013 is the use of student’s handbook that are equipped with a teacher's handbook. The approach in this research is descriptive qualitative (Library Research). The data in this study are related to the quality of teacher’s and student’s handbook. The source of the data was obtained from the textbooks of teachers and students of Arabic class XI curriculum of 2013 printed by the Ministry of Religion. Data collection techniques through documentation. Meanwhile, the data analysis technique is through clarification and description. Based on the analysis that has been done, the results of this study indicate that the quality of teacher and student textbooks is in the good category. However, there are several things that need to be completed, such as writing the address of the photo or image where it was obtained in the discussion of the material.